Ocular Artifact Removal Method Based on the Wavelet and ICA Transform - Erkan, Erdem; Erkan, Yasemin; Erkan, Yasemin; Erkan, Erdem (Akif AKGUL, 2023)
The electroencephalogram is a promising tool used to unravel the mysteries of the brain. However, such signals are often disturbed by ocular artifacts caused by eye movements. In this study, Independent Component Analysis and Wavelet Transform based ocular artifact removal method, which does not need reference signals, is proposed to obtain signals free from ocular artifacts. With our proposed method, firstly, the ocular artifact regions in the time domain of the signal are detected. Then the signal is decomposed into its components by independent component analysis and independent components containing artifacts are detected. Wavelet transform is only applied to these components with artifact. Zeroing is applied to the parts of the wavelet coefficients obtained as a result of the wavelet transform corresponding to the ocular artifact regions in the time domain. Finally, the clean signal is obtained by inverse Wavelet transform and inverse Independent Component Analysis methods, respectively. The proposed algorithm is tested on a real data set. The results are given in comparison with the method in which the zeroing is applied to the classical independent components. According to the results, it is seen that most of the signal is not affected by the zeroing and the neural part of the EEG signals is successfully preserved. © 2023 Elsevier B.V., All rights reserved.
Ocular Artifact Removal Method Based on the Wavelet and ICA Transform
Keywords: Brain Computer Interface; Component Analysis; Electroencephalography; Electrooculogram Independent; Wavelet Transform